Profile of facial trauma in older adults cared for at a tertiary hospital of the Brazilian Federal District - Matheus Almeida Barbosa; Daniel Saraiva de Paula; Attio Augusto Guimarães da Silva; Leonardo Paiva Marques de Souza; Isabela Gomes de Sena Ribeiro; Everton Luis Santos da Rosa; Alexandre Franco Miranda; Lucy de Oliveira Gomes (Brazilian Society of Geriatrics and Gerontology, 2022)
OBJECTIVES: The phenomenon of population aging and the remarkable inclusion of older adults in the economically active population has increased their participation in injuries and accidents, including facial trauma. The purpose of this study was to analyze the prevalence, etiology, and treatment of facial trauma in the older population of the Brazilian Federal District, as well as the gender, etiology, type of trauma, and treatment strategy regarding different age groups (60-69 years, 70-79 years, and 80 years or older). METHODS: This is a retrospective quantitative descriptive study using electronic medical records (Trackcare system) of older patients (aged = 60 years) assisted at the Emergency Department of a tertiary hospital of the Federal District between 2016 and 2017 due to facial trauma. RESULTS: Out of 2382 records of patients with facial trauma, 139 (5.8%) were aged over 60 years. The main causes of facial trauma were falls, both in male and female patients. Facial contusion was the main diagnosis of facial trauma (25.2%), followed by fractures of the jaw (16.5%) and zygomatic complex (15.8%). Conservative treatment was the most common strategy adopted in the Emergency Department of Oral and Maxillofacial Surgery and Traumatology. CONCLUSIONS: This study showed a high prevalence of facial trauma in the geriatric population. Etiological factors such as falls and car accidents were highlighted in the studied groups. Conservative treatment and local guidelines were the preferred therapeutic approaches. Owing to the growth trend of the older population in the upcoming decades, exposure to risk factors for facial trauma tends to grow, thus requiring greater attention and specific knowledge from health professionals.